(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
There are determined empirically defined methods of organizing the communicative space in Ukrainian diary discourse, the types of diary communication are revealed, is traced the lingual psycho and mental activity of the communicant-producer and communicant recipient in the process of exchange of data carriers and reciprocal effect with the aid of the signs of natural language.